Measurement of Right Atrial Volume and Diameters in Healthy Nepalese with Normal Echocardiogram - Karki, DB; Pant, S; Yadava, SK; Vaidya, A; Neupane, DK; Joshi, S (Kathmandu University Medical Journal, 2015)
Background The size of right atrium is expected to be different in diverse healthy ethnic groups. It is important to know the normal size of right atrium in our healthy population.Objective The study aimed to find out the normal values of right atrial volume, right atrial short axis diameter and right atrial long axis diameter in healthy Nepalese population with normal echocardiographic findings. It also looked at correlations between right atrial dimensions and the right atrial volume.Method Verbal consent was taken from all the participants. One hundred participants between the age of 18 and 60 years with normal echocardiographic findings and without any chronic disease were included in this study. Right atrial volume was measured by using area length method. Right atrial short axis diameter and Right atrial long axis diameter were measured in the four chamber view.Result The mean right atrial volume was 23.64±5.36 ml (range 11.30 - 40.00 ml).The range of right atrial short axis diameter and right atrial long axis diameter were 1.34-3.80 cm and 2.4-4.7 cm respectively.Conclusion The size of right atrium in the Nepalese population is smaller compared to western population. Male right atrial volume size is greater than female in Nepalese population similar to western population. The findings of normal value of right atrial volume and right atrial diameter in Nepalese population will help the physician to assess patients with various conditions affecting the right atrium.Kathmandu University Medical Journal Vol.12(2) 2014: 110-112